Reactive oxygen species: from health to disease - Brieger, Katharine; Schiavone, Stefania; Miller Jr, Francis J.; Krause, Karl-Heinz (Swiss medical weekly, 2012)
Upon reaction with electrons, oxygen is transformed into reactive oxygen species (ROS). It has long been known that ROS can destroy bacteria and destroy human cells, but research in recent decades has highlighted new roles for ROS in health and disease. Indeed, while prolonged exposure to high ROS concentrations may lead to non-specific damage to proteins, lipids, and nucleic acids, low to intermediate ROS concentrations exert their effects rather through regulation of cell signalling cascades. Biological specificity is achieved through the amount, duration, and localisation of ROS production. ROS have crucial roles in normal physiological processes, such as through redox regulation of protein phosphorylation, ion channels, and transcription factors. ROS are also required for biosynthetic processes, including thyroid hormone production and crosslinking of extracellular matrix. There are multiple sources of ROS, including NADPH oxidase enzymes; similarly, there are a large number of ROS-degrading systems. ROS-related disease can be either due to a lack of ROS (e.g., chronic granulomatous disease, certain autoimmune disorders) or a surplus of ROS (e.g., cardiovascular and neurodegenerative diseases). For diseases caused by a surplus of ROS, antioxidant supplementation has proven largely ineffective in clinical studies, most probably because their action is too late, too little, and too non-specific. Specific inhibition of ROS-producing enzymes is an approach more promising of clinical efficacy.